2020
DOI: 10.3389/fmicb.2020.02007
|View full text |Cite
|
Sign up to set email alerts
|

Nanopore MinION Sequencing Reveals Possible Transfer of blaKPC–2 Plasmid Across Bacterial Species in Two Healthcare Facilities

Abstract: Carbapenemase-producing Enterobacteriaceae are a major threat to global public health. Klebsiella pneumoniae carbapenemase (KPC) is the most commonly identified carbapenemase in the United States and is frequently found on mobile genetic elements including plasmids, which can be horizontally transmitted between bacteria of the same or different species. Here we describe the results of an epidemiological investigation of KPC-producing bacteria at two healthcare facilities. Using a combination of shortread and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 80 publications
1
21
0
Order By: Relevance
“…This might be due to limitations in our draft assemblies. In two recent studies, the authors demonstrated ARG-carrying plasmid transfer in clinical settings between bacteria of the same or different species, emphasizing the significance of revealing potential plasmid-mediated outbreaks to efficiently track horizontal ARG transmission in hospitals [ 44 , 45 ]. Once phages could transfer ARGs among their hosts we also employed Phaster [ 46 ], a web-service for phage identification, to search for the co-occurrence of phages and ARGs, but ARGS were found in phage-related regions of the genomes ( Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…This might be due to limitations in our draft assemblies. In two recent studies, the authors demonstrated ARG-carrying plasmid transfer in clinical settings between bacteria of the same or different species, emphasizing the significance of revealing potential plasmid-mediated outbreaks to efficiently track horizontal ARG transmission in hospitals [ 44 , 45 ]. Once phages could transfer ARGs among their hosts we also employed Phaster [ 46 ], a web-service for phage identification, to search for the co-occurrence of phages and ARGs, but ARGS were found in phage-related regions of the genomes ( Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…KPC-2, the most common CPase in the USA, emerged in North Carolina in 1996 52 , and spread within the USA 53,54 , South America 55 , Europe 30,56 , Israel 57 , South Africa 58 , Asia 1,[59][60][61] , and worldwide 30 . CRE is predominantly due to KPC-2 on plasmids or other MGEs (e.g., insertion sequences, and phage-related sequences) 62,63 . In Brazil, KPC-2 is the most common CPase, carried on plasmids among K. pneumoniae belonging to different international lineages (e.g., sequence type (ST)258, ST101, and ST15) 64 .…”
Section: Carbapenemases (Cpases) and International Spreadmentioning
confidence: 99%
“…3 ). In two recent studies, authors demonstrate ARG-carrying plasmids transfer in clinical settings between bacteria of the same or different species, which emphasize the significance of revealing potential plasmid-mediated outbreaks to efficiently track ARGs horizontal transmission in hospitals (30, 31).…”
Section: Resultsmentioning
confidence: 97%